Modeling and Control for Dynamic Positioned Marine Vessels in Drifting Managed Sea Ice - Kjerstad, Øivind Kåre; Skjetne, Roger (Modeling, Identification and Control: A Norwegian Research Bulletin, 2014)
This paper presents a development framework for dynamic positioning control systems for marine vessels in managed ice. Due to the complexity of the vessel-ice and ice-ice interactions a configurable high fidelity numerical model simulating the vessel, the ice floes, the water, and the boundaries is applied. The numerical model is validated using experimental data and coupled with a control application incorporating sensor models, control systems, actuator models, and other external dynamics to form a closed loop development platform. The ice drift reversal is simulated by moving the positioning reference frame in an elliptic trajectory, rather than moving each individual ice floe. A control plant model is argued, and a control system for managed ice is proposed based on conventional open water design methods. A case study shows that dynamic positioning in managed ice is feasible for some moderate ice conditions. (c) 2014 Norwegian Society of Automatic Control. Creative Commons Attribution 3.0 Unported (CC BY 3.0) license. See: http://creativecommons.org/licenses/by/3.0/.